Validation of the Slovenian version of the Movement imagery questionnaire for children (MIQ-C) - Šlosar, Luka (Zdravstveno varstvo, 2023)
Purpose: The ability to perform motor imagery has been shown to influence individual athletic performance and rehabilitation. Recent evidence supports its potential as a training tool to improve motor skills in children. Although there is a standardized assessment of the imagery abilities in Slovenian-speaking adults, there is currently no validated instrument for use with Slovenian children. Therefore, the aim of the present study was to conduct a linguistic validation study of the movement imagery questionnaire for children (MIQ-C). Methods: A total of 100 healthy children (mean age 10.3±1.3 years; 50 female) were assessed with a Slovenian version of the MIQ-C at Day 1 and Day 8. Inter-day agreement was examined using intraclass correlation coefficients (ICC). Construct validity and internal consistency were assessed using a Cronbach’s alpha coefficient and exploratory – confirmatory factor analysis, respectively. Results: The test-retest ICC were very high for all three scales examined (ICCKI=0.90; ICCIVI=0.92; ICCEVI=0.90). Excellent internal consistency (up to 0.90) was found for kinaesthetic and both visual imageries. Confirmatory analysis confirmed a three-factorial structure of the MIQ-C. Conclusions: The Slovenian version of the MIQ-C proved to be highly reliable and valid in assessing children’s motor imagery abilities, and as such for use with Slovene-speaking children. Moreover, this standardized instrument can be a helpful tool in training and rehabilitation practice with children aged 7-12 years.
Keywords: gibalne predstave; imagery ability; jezikovna validacija; linguistic validation; mental practice; mentalna vadba; questionnaires; vprašalniki